Modelling of hydrodynamics in heterogeneous bubble column - Mohd Shahimie, Selamat (2010)
The applications of bubble columns are very important as multiphase contactors and reactors in process industry. They are wide and extensively used in chemical, petrochemical and biochemical industries. The advantages of bubble column are low maintenance and operating cost due to the compactness and no moving part. They also have an excellent mass and heat transfer characteristic or high heat and mass transfer coefficients, and high durability of catalyst or packing material. It is important to understand the nature of hydrodynamics and operational parameters to characterize their operation including pressure drop, gas superficial velocity, bubble rise velocity, etc., to do the design and scale-up process. Although experimental methods are available to elucidate the multiphase flow in bubble column by the means of advanced experimental methods i.e. X-ray tomography and laser doppler anemometry, the experimental setup is often expensive to develop. Alternatively, the computational fluid dynamics can be used to evaluate the performance of bubble column at lower cost compared to experimental setup. In this work commercial CFD software, FLUENT 6.3 was employed for modeling of gas liquid flow in a bubble column. Multiphase simulations were performed using an Eulerian-Eulerian two-fluid model and the drag coefficient of spherical and distorted bubbles was modeled using the Tomiyama (1995) and Schiller-Naumann (1935) models. The effect of the void fractions on the drag coefficient was modeled using the correlation by Behzadi (2004). The CFD predictions were compared to the experimental measurement adopted from literature. The CFD predicts the turbulent kinetic energy, gas hold-up and the liquid axial velocity fairly well, although the results seem to suggest that further improvement on the interfacial exchange models and possibly further refinement on the two-fluid modeling approaches are necessary especially for the liquid axial velocity and turbulent kinetic energy. It is clear from the modeling exercise performed in this work that CFD is a great method for modeling the performance of bubble column. Furthermore, the CFD method is certainly less expensive than the experimental characterization studies.